2004
DOI: 10.1097/01.jcp.0000125680.89843.a6
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Metabolism of Citalopram in Plasma and Cerebrospinal Fluid of Depressive Patients

Abstract: Plasma and cerebrospinal fluid (CSF) concentrations of the enantiomers of citalopram (CIT), its N-demethylated metabolite demethylcitalopram (DCIT) and its deaminated metabolite citalopram propionic acid derivative (CIT-PROP) were measured in plasma and CSF in 22 depressed patients after a 4-week treatment with 40 mg/d citalopram, which was preceded by a 1-week washout period. CSF 5-hydroxyindoleacetic acid (5-HIAA) and homovanillic acid (HVA) were measured at baseline and after the 4-week CIT medication perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
34
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 44 publications
8
34
0
Order By: Relevance
“…The knowledge that neuronal uptake blockade following antidepressant administration occurs rapidly but therapeutic effects may take from 2 to 6 weeks to occur 70 has been difficult to reconcile both in terms of the etiology of the disease and the therapeutic mechanism of SSRIs. In agreement with our results documenting a reduction in internal jugular venous overflow of 5-HIAA following SSRI administration, improvement in symptoms coupled with a reduction in CSF 5-HIAA levels in patients with MDD following therapy with citalopram, 71,72 venlafaxine hydrochloride, 73 fluvoxamine, and fluoxetine 43,74 have previously been described. Citalopram administration in chronically stressed rats normalizes the elevated expression of tryptophan hydroxylase.…”
Section: Commentsupporting
confidence: 80%
“…The knowledge that neuronal uptake blockade following antidepressant administration occurs rapidly but therapeutic effects may take from 2 to 6 weeks to occur 70 has been difficult to reconcile both in terms of the etiology of the disease and the therapeutic mechanism of SSRIs. In agreement with our results documenting a reduction in internal jugular venous overflow of 5-HIAA following SSRI administration, improvement in symptoms coupled with a reduction in CSF 5-HIAA levels in patients with MDD following therapy with citalopram, 71,72 venlafaxine hydrochloride, 73 fluvoxamine, and fluoxetine 43,74 have previously been described. Citalopram administration in chronically stressed rats normalizes the elevated expression of tryptophan hydroxylase.…”
Section: Commentsupporting
confidence: 80%
“…Based on the substrate depletion experiments, CL int due to SCIT PROP formation was approximately 70% of the CL int accounted for by SDCIT formation. However, in line with previous studies (Bondolfi et al, 1996(Bondolfi et al, , 2000Nikisch et al, 2004), plasma concentrations of SCIT PROP exceeded those of SDCIT in most of the patients. This finding indicates that subsequent elimination of SCIT PROP, probably via glucuronidation (Oyehaug et al, 1984;Dalgaard and Larsen, 1999), is slower than for SDCIT.…”
Section: Novel Cyp2c19-mediated Metabolic Pathway Of S-citalopramsupporting
confidence: 76%
“…Although the distributional characteristics of this metabolite are essentially unknown, a study by Nikisch et al (2004) reported that SCIT PROP was present in the cerebrospinal fluid of patients treated with racemic CIT. However, the pharmacodynamic properties of SCIT PROP were not investigated, and a potential contribution from SCIT PROP to the clinical effects or side effects of SCIT treatment is therefore unknown.…”
Section: Novel Cyp2c19-mediated Metabolic Pathway Of S-citaloprammentioning
confidence: 99%
See 1 more Smart Citation
“…These values are within clinically relevant therapeutic ranges (Perry et al, 1994;Nikisch et al, 2004). There were no significant differences between treatment groups in trials to criterion for the SD task on the training day (F 1,39 ¼ 0.526, p ¼ 0.47 for Stress; F 2,39 ¼ 0.902, p ¼ 0.41 for drug).…”
Section: Experiments 2: Effect Of Chronic Antidepressant Drug Treatmenmentioning
confidence: 56%